(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the need for a competent approach to teaching digital tools and resources to undergraduate students of pedagogical education. The selection criteria are considered, the analysis of classifications of digital resources and tools is given, the authorʼs classifications are presented.